Stressing the recurrent laryngeal nerve during thyroidectomy. Issue 12 (19th March 2015) - Serpell, Jonathan W.; Lee, James C.; Chiu, Wing K.; Edwards, Glenn
Abstract: Background: In thyroidectomy, little has been reported on the differential recurrent laryngeal nerve (RLN) palsy rates between the left and right sides. Even less is known about the potential differences causing these differential rates. This study reports the left versus right RLN palsy rates of total thyroidectomy cases in a single institution, relating them to the comparative stiffness of the left and right porcine RLNs. Computed stress modelling was also used to estimate the differential levels of tension within each RLN. Methods: For the comparison of the left and right RLN palsy rates, 1926 cases of total thyroidectomy (between 2007 and 2013) from the Monash University Endocrine Surgery Unit were included. Stiffness of porcine RLNs was experimentally determined by measuring nerve extension against incremental increase in load. Additionally, the tension of intraoperatively stretched RLNs was estimated by computer modelling. Results: The left RLN had a palsy rate of 0.9% (18/1926), which was significantly lower ( P = 0.025) than the right RLN palsy rate of 1.8% (34/1926). The left porcine RLN was 22% stiffer than the right RLN ( P = 0.004). The stress modelling estimated that at the apex of the artificial RLN genu during anteromedial rotation of the thyroid lobe, the right RLN experiences twice the tension experienced by the left RLN. Conclusion: The stiffer left RLN and the higher tension generated in the right RLN during thyroidectomy may jointly contribute to the higher right RLN palsy rate.